2022
DOI: 10.3390/cells11213456
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Early Response of Lens Epithelial Cells to Lens Injury

Abstract: Cataracts are treated by lens fiber cell removal followed by intraocular lens (IOL) implantation into the lens capsule. While effective, this procedure leaves behind numerous lens epithelial cells (LECs) which undergo a wound healing response that frequently leads to posterior capsular opacification (PCO). In order to elucidate the acute response of LECs to lens fiber cell removal which models cataract surgery (post cataract surgery, PCS), RNA-seq was conducted on LECs derived from wild type mice at 0 and 6 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 98 publications
2
2
0
Order By: Relevance
“…This approach made it possible to focus on the response of the injured epithelium and its associated resident immune cells in the absence of any immune contribution from outside of the lens. In this reductionist lens wounding model, we found that the immediate early transcription factors were induced within 1 h of injury, including the transcription factors Egr1 and FosB (Supplemental File S1), which had been previously reported for the mouse model at 6 h post cataract surgery [27]. Also, consistent with studies performed at later times post lens wounding, we found that pro-inflammatory cytokine genes are induced within 1 h post lens wounding, which at this early time included the chemokine CCL4, also known as macrophage inflammatory protein.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This approach made it possible to focus on the response of the injured epithelium and its associated resident immune cells in the absence of any immune contribution from outside of the lens. In this reductionist lens wounding model, we found that the immediate early transcription factors were induced within 1 h of injury, including the transcription factors Egr1 and FosB (Supplemental File S1), which had been previously reported for the mouse model at 6 h post cataract surgery [27]. Also, consistent with studies performed at later times post lens wounding, we found that pro-inflammatory cytokine genes are induced within 1 h post lens wounding, which at this early time included the chemokine CCL4, also known as macrophage inflammatory protein.…”
Section: Discussionsupporting
confidence: 73%
“…The cytokines induced are consistent with a role in the activation of an innate immune response, with cytokine expression preceding the detection of neutrophils with the post-cataract surgery lens tissue [9]. The upregulation of pro-inflammatory cytokines was also detected in studies performed at 6 h post mouse cataract surgery [27].…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…It is currently unknown how Atf4 transcript levels are regulated in the developing lens, the precise time point in lens development when ATF4 function becomes necessary, the key mechanisms that fine-tune its function to drive appropriate lens amino acid levels, or whether/how it interfaces with HIF1a during adaption of the lens to chronic tissue hypoxia. Notably, Atf4 mRNA levels also upregulate sharply in lens epithelial cells by 6 h after lens injury and remain elevated for several days, while Hif1a mRNA levels decrease in injured LECs over this same time frame [22,61,108,109]. As ATF4 is best known as a mediator of cellular responses to acute stress in other tissues [26], the lens may be an ideal system to investigate how the diverse functions of Atf4 are differentially regulated during both normal tissue development and as a consequence of injury responses.…”
Section: Conclusion and Outstanding Questionsmentioning
confidence: 96%